2021
DOI: 10.1590/1516-4446-2020-1111
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-long-term lithium therapy: all-important matters and a case of successful 50-year lithium treatment

Abstract: This paper discusses essential issues related to long-term lithium therapy and presents a case of successful 50-year lithium treatment. Lithium is currently regarded as the drug of choice for preventing manic and depressive recurrences in bipolar disorder. In 1/3 of patients with bipolar disorder, long-term monotherapy with lithium can completely prevent recurrences of abnormal mood. Numerous clinical and psychosocial factors associated with a good response to lithium have been described. Lithium is more effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 60 publications
1
19
0
3
Order By: Relevance
“…Lithium poisoning has a low mortality rate and persistent cerebellar neurological deficits are uncommon in uncomplicated acute poisoning [ 16 ]. Same observations were reported for appropriate lithium doses with rare cardiac manifestations [ 17 ], gastro-intestinal upset [ 18 ] and endocrine manifestations [ 19 ]. Moreover, low doses of lithium are correlated with lower side-effects [ 20 ] and two reviews advocate the use of lithium therapy despite its potential side effects [ 21 , 22 ].…”
Section: Introductionsupporting
confidence: 67%
“…Lithium poisoning has a low mortality rate and persistent cerebellar neurological deficits are uncommon in uncomplicated acute poisoning [ 16 ]. Same observations were reported for appropriate lithium doses with rare cardiac manifestations [ 17 ], gastro-intestinal upset [ 18 ] and endocrine manifestations [ 19 ]. Moreover, low doses of lithium are correlated with lower side-effects [ 20 ] and two reviews advocate the use of lithium therapy despite its potential side effects [ 21 , 22 ].…”
Section: Introductionsupporting
confidence: 67%
“…Swedish national recommendations derive from international guidelines and holds lithium as the first-line option for long-term treatment (Adler et al 2014 ). Lithium was first shown to be effective in mania in 1949 (Cade 1949 ) and has been known to prevent mood episodes in BD since the 1960s (Baastrup 1964 ; Hartigan 1963 ; Ferensztajn-Rochowiak et al 2020 ). A meta-analysis of randomized controlled trials (RCT) with lithium maintenance treatment (n = 1580, seven trials) demonstrated significant relative risk reductions of 34% for any type of recurrent episodes, 48% for manic episodes, and 22% for depressive episodes (Severus et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Literature supports Lithium, as thesuccessful drug,for depression 1 .Research conducted by de Cerqueira et al 2,3 (2008) had reported that lithium causes cerebellar degeneration due to significant neuronal loss. At therapeutic doses the most common adverse effects like tremors, incoordination 4 were reported.…”
Section: Introductionmentioning
confidence: 97%